Dietary Protein Requirement for Optimising Growth Responses of Asian Cichlid, Etroplus suratensis (Bloch) - V., Jayaprakas; S., Sunil Kumar (Fishery Technology, 2025)
Supplementary diets having three levels of protein viz., 30, 35 and 40% were fed to E. suratensis for a period of 120 days. Growth, feed conversion efficiency, digestive enzyme activity, nucleic acid content and carcass proximate composition were evaluated. Highly significant (p